Neuropathic Itch: Routes to Clinical Diagnosis - Pereira, Manuel Pedro; Wiegmann, Henning; Agelopoulos, Konstantin; Ständer, Sonja (Frontiers in Medicine, 2021)
Neuropathic itch occurs due to damage of neurons of the peripheral or central nervous system. Several entities, including metabolic, neurodegenerative, orthopedic, infectious, autoimmune, malignant and iatrogenic conditions, may affect the somatosensory system and induce neuropathic itch. Due to the complex nature of neuropathic itch, particularly concerning its clinical presentation and possible etiological factors, diagnostic work-up of this condition is challenging. A detailed medical history, especially in regard to the itch, and a comprehensive physical examination are relevant to detect characteristic signs and symptoms of neuropathic itch and to rule out other possible causes for chronic itch. Complementary diagnostic exams, especially laboratory tests, determination of the intraepidermal nerve fiber density via a skin biopsy and radiological examinations may be indicated to confirm the diagnosis of neuropathic itch and to identify underlying etiological factors. Functional assessments such as quantitative sensory testing, nerve conduction studies, evoked potentials or microneurography may be considered in particular cases. This review article provides a comprehensive overview of the diagnostic work-up recommended for patients with neuropathic itch.